Analisis Implementasi Standar Akuntansi untuk Meningkatkan Transparansi Laporan Keuangan dalam Instansi Syariah - Tasya Tasya; Riska Anisa; Andi Risma; Masyhuri Masyhuri (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Transparency of financial reporting is a strategic aspect in supporting the implementation of good governance in sharia institutions. Sharia accounting standards serve as guidelines in the process of recognizing, measuring, presenting, and disclosing financial information, thus producing higher quality, relevant, and reliable financial reports. This study aims to analyze the role of accounting standards implementation in improving the transparency of sharia institutions' financial reports. This study uses a literature study method with a qualitative descriptive approach through a review of various relevant scientific journals, regulations, and Sharia Financial Accounting Standards (SAK) applicable in Indonesia. The results of the study indicate that consistent application of sharia accounting standards can improve the quality of financial reporting, strengthen accountability, and increase stakeholder trust in sharia institutions. Transparency of financial reporting can be achieved through complete disclosure of information, compliance with sharia principles, and presentation of reports in accordance with Sharia PSAK. However, the implementation of sharia accounting standards still faces various obstacles, such as limited human resource competency, low understanding of applicable standards, and a suboptimal financial reporting system. Therefore, strengthening human resource competencies, enhancing oversight, and optimizing the implementation of Sharia Financial Accounting Standards (PSAK) are necessary to promote greater transparency and accountability in financial reporting. Research findings demonstrate that the implementation of Sharia accounting standards plays a crucial role in improving the quality of financial reporting and strengthening the sustainability and trust of Sharia institutions.